Transforming urban energy: developments and challenges in photovoltaic integration - Schmid, Cordula V.; Ngagoum Ndalloka, Zita; Kośny, Jan (Frontiers in Sustainable Cities, 2025)
As urban areas expand and the global focus on sustainability intensifies, integrating solar energy into urban systems has become a critical area of research and application. According to the United Nation Dept. of Economics and Social Affairs, in 2022, more than half of the world’s population already resided in urban areas, increasing the global electricity demand to approximately 30,000 terawatt-hours (TWh). At the same time, predictions indicate that by 2050, about 2/3-rd of the global population will live in urban areas, adding there around 2.5 billion people. In this light, providing a sustainable and reliable electric power supply is becoming a major challenge for city planning bodies, governments, and power utility companies. Utilization of architectural surfaces and components of urban infrastructure for renewable energy generation is becoming an often-considered potential solution. Furthermore, pairing PV systems with advanced energy storage solutions, including batteries, stabilizes supply–demand fluctuations, while digital tools such as Internet of Things (IoT), Artificial Intelligence (AI), and digital twins enhance system efficiency and grid management. These approaches are adding a variety of power generation systems, electrical control and energy storage components, and hardware, directly, to buildings and, on a broader scale, to urban districts. Community solar projects provide access to renewable energy in densely populated areas, particularly where rooftop space is limited. Additionally, integrating solar technologies with electric vehicle charging stations, green roofs, and urban agriculture systems demonstrates the multifunctionality of PV systems. This article explores strategies for urban solar expansion, emphasizing urban energy planning, advanced energy storage, digital tools, community solar projects, and integration with other urban systems. The potential of solar energy technologies in urban environments is discussed, from the perspective of supporting the transition to sustainable, energy-efficient cities while addressing technical, economic, and policy challenges.